2021
DOI: 10.1021/acsenergylett.1c01447
|View full text |Cite
|
Sign up to set email alerts
|

Cycling Performance and Limitations of LiNiO2 in Solid-State Batteries

Abstract: Solid-state batteries (SSBs) have been touted as the next major milestone for electrochemical energy storage, improving safety and enabling higher energy densities. LiNiO 2 (LNO) has long been considered a promising cathode material; however, its commercial implementation is complicated by stability issues, including reactivity toward the electrolyte components. To address this, a detailed study probing the electrochemical behavior of LNO in pellet-stack SSB cells, in combination with argyrodite Li 6 PS 5 Cl s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…These changes in the ED profiles of argyrodite-structured SE indicate that the SE exhaled the products, such as LiCl and Li2S, and decomposed into an amorphous phase. These results are similar to those previously reported, 2,12 and it is significant that the HPC parameters further support them in this study. Conversely, when looking at the active material of NCM523, a significant change in particle size was observed in the TEM image at the highest potential of 4.65 V vs. Li/Li + .…”
Section: Accepted M Msupporting
confidence: 93%
See 1 more Smart Citation
“…These changes in the ED profiles of argyrodite-structured SE indicate that the SE exhaled the products, such as LiCl and Li2S, and decomposed into an amorphous phase. These results are similar to those previously reported, 2,12 and it is significant that the HPC parameters further support them in this study. Conversely, when looking at the active material of NCM523, a significant change in particle size was observed in the TEM image at the highest potential of 4.65 V vs. Li/Li + .…”
Section: Accepted M Msupporting
confidence: 93%
“…2 However, the decomposition reactions gradually proceed at the interface of sulfide SE/NCM in conditions such as a high temperature environment, high cathode potential, and after a long-term charge/discharge cycle testing. 2,11,12 Elucidating the not-fully-understood decomposition side reactions in more detail will be an important finding for further material development and improvement of battery performance of ASSBs using sulfide SE in the future.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that (chemo‐)mechanical degradation within the cathode does not play a critical role in the differences in cyclability between the bare and coated NCM85 CAMs in these cells. [ 8 ] Additionally, XRD data collected from the cathode composites in the pristine state and after cycling showed that the bulk structure of Li 6 PS 5 Cl remains stable (see Figure S22 and Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…While the pronounced doublet at 161.7/162.9 eV is characteristic of the PS 4 3− units of the argyrodite structure, that at a lower binding energy (160.3/161.4 eV) represents Li 2 S impurities (or “free” S 2− ions). [ 8,18,45 ] The other two minor doublets located at higher binding energies (162.9/164.1 and 163.7/164.9 eV) can be assigned to various compounds, including anionic frameworks that thiophosphate phases can pass through upon oxidative decomposition toward the formation of P 2 S 5 (e.g., P 2 S 7 4− , P 2 S 6 2− ) and “S 0 ” species, such as long‐chain polysulfides. [ 8,18 ] The P 2p spectrum showed two doublets at 132.0/132.8 and 133.0/133.9 eV, representing the PS 4 3− units and the aforementioned degradation products and/or lithium phosphate, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation